Isolation of a Dissimilatory Iodate-Reducing Aromatoleum sp. From a Freshwater Creek in the San Francisco Bay Area - Reyes-Umana, Victor; Kretschmer, Jessica; Coates, John D. (Frontiers in Microbiology, 2022)
Recent reports of dissimilatory iodate-reducing microorganisms (DIRM) have arisen from studies of bacteria in marine environments. These studies described the physiology and distribution of DIRM while also demonstrating their presence in iodine-rich marine environments. We posited that despite lower iodine concentrations, terrestrial and freshwater ecosystems should also harbor DIRM. We established numerous enrichments from coastal and freshwater environments that actively remove amended iodate. We describe the physiology and genome of a new DIRM isolate, Aromatoleum toluclasticum sp. TC-10, emerging from a freshwater creek microcosm. Like other DIRM, A. toluclasticum sp. TC-10 couples acetate oxidation to iodate reduction with a concomitant increase in the OD600. Our results indicate that A. toluclasticum sp. TC-10 performs dissimilatory iodate reduction (DIR) using the recently described iodate reductase (Idr). We provide further evidence of horizontal gene transfer of the idr genes by demonstrating the lack of Idr in the closely related A. toluclasticum sp. MF63 and describe the heterogeneity of the accessory proteins associated with the iodate reduction island (IRI). These observations provide additional evidence that DIR is a horizontally acquired metabolism with broad environmental distribution beyond exclusively marine environments.